Inovasi E-LKPD Berbantuan Liveworksheets Materi Daerahku Kebanggaanku sebagai Penguatan Pembelajaran IPAS di Sekolah Dasar - Filza Mulya Rahma; Yusra Nasution; Wildansyah Lubis; Husna Parluhutan Tambunan; Waliyul Maulana Siregar (Paedagogi: Jurnal Kajian Ilmu Pendidikan (e-journal), 2025)
This study aims to develop and examine the validity, practicality, and effectiveness of a Liveworksheets-based Electronic Student Worksheet (E-LKPD) on the topic "My Proud Region" for fifth-grade students at SD Negeri 2 Pasar Aceh Singkil. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The feasibility of the product was assessed by a content expert, media expert, and education practitioner. The results showed an average score of 82.6% from the content expert (categorized as “valid”), 87% from the media expert (“very valid”), and 81.3% from the education practitioner (“very practical”). The product was implemented through a pre-test and post-test, showing a significant increase in students' average score from 56.1 to 90.18. The N-gain score was 0.79, which falls into the high category, indicating that the E-LKPD is effective in improving students' learning outcomes. The final evaluation revealed that the product was well-received by both students and teachers and provided a more engaging, interactive, and efficient learning experience. This study concludes that the Liveworksheets-based E-LKPD is suitable for use as an interactive learning medium in elementary schools.